AB0408 An investigation of vitamin d status in systemic lupus erythematosus patients residing in northern ireland: its relationship with disease activity and bone mineral density. (23rd January 2014) - Breslin, L. C.; Ball, E.; Armstrong, D.; Bell, A.; Magee, P.; Laird, E.; Wallace, J.; McSorley, E.
Abstract : Background: Vitamin D has the potential to modulate the immune system for patients with systemic lupus erythematosus (SLE) 1, and which could potentially lead to improved clinical outcomes. Observational data have suggested a relationship between vitamin D and disease activity 2 . This observation has been confirmed by vitamin D3 supplementation studies, where positive immunological effects were reported in SLE patients 3 . Additionally a placebo controlled trial supplementing SLE patients with vitamin D3 identified a positive effect on inflammation and haemostatic markers as well as improvements in disease activity 4 . Research examining the relationship between vitamin D and bone mineral density (BMD) in SLE patients is limited, albeit a study has suggested a link between disease activity and BMD in SLE patients 5 and thereby suggesting flares in disease activity has a negative effect on BMD. Objectives: To examine for relationships between vitamin D and disease activity, damage and BMD. Methods: A total of 52 SLE patients were recruited onto an observational study during the winter (November-March) and followed up during the summer months (June-July) (n=50). Total 25-hydroxyvitamin D (25(OH)D) concentration was measured using the liquid chromatography mass spectrometry method (MassChrom ®, Chromsystems Gmbh, Heimburgstrasse, Germany) and BMD was measured at the lumbar spine and femur by dual energy X-ray absorptiometry (Lunar iDXA™, UK). Disease activity and damage were assessed using Systemic Lupus Activity Measure (SLAM), British Isles Lupus Assessment Group (BILAG), Systemic Lupus Erythematosus Disease Activity Index (SELENA SLEDAI) and Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR). Results: Mean (SD) 25(OH)D concentrations in winter (26.9 (16.2) nmol/L) and summer (28.7 (16.7) nmol/L) were not different ( P =0.439), nor were differences observed between disease activity and damage. During the winter, but not during the summer, vitamin D was a significant predictor of BILAG ( r =-0.307; P =0.027) and SELENA SLEDAI (β=-0.074; SE=0.036; P =0.044), controlling for age, BMI and medications. Osteoporosis and osteopenia was present in some 4 (8%) and 21 (45%) SLE patients respectively and there were no relationships observed between disease activity and BMD. Conclusions: Vitamin D inadequacy was prevalent throughout the year and undiagnosed osteoporosis was apparent in this cohort, and, therefore, suggesting routine screening of both is warranted. Wintertime vitamin D status was a predictor of disease activity at that time of year. There was no relationship, however, observed between disease activity and BMD. The lack of seasonal variability in vitamin D status might suggest sun avoidance by the SLE patients; emphasising the importance of obtaining adequate vitamin D intake from the diet and supplements for SLE patients. References: Marques et al. Revista Brasileira de Reumatologia. 2010;50(1):67-80. Breslin, et al. Proceedings of the Nutrition Society. 2011 Nov;70(4):399-407. Terrier, et al . Arthritis Research and Therapy. 2012 Oct 17;14(5). Abou-Raya A, et al. Journal of Rheumatology, 2012. Zhang et al. Zhonghua Yi Xue Za Zhi, 2012 Sep 4;92(33):2331-4. Disclosure of Interest: None Declared